Happiness Curriculum in Schools of Delhi A Study of Teachers’ Belief and its Relevance in School System - Dutta, Indrajeet; Chabra, Sonal (JOURNAL OF INDIAN EDUCATION, 2021)
Curriculum, in the simplest terms, means the experiences and exposure to learners not only in the academic areas but also in the areas which are equally important like games, sports, vocational activities, dance, music, and performing and visual arts etc. It is done to for the holistic development of the child. However, the present education system and its curriculum is generally accused of promoting academics and overlooking the development of traits like resilience, happiness and life skills among others. The introduction of Happiness Curriculum in schools in Delhi was a step taken to provide for this gap. Through this paper, the researchers are sharing their small research undertaken to study the beliefs of teachers about the Happiness Curriculum in schools. Further, research also explored the relevancy of Happiness Curriculum in current school scenario. The lockdown limited our interaction to only 12 teachers. A semi-structured questionnaire was used to collect data. Further, telephonic interview was conducted with few school coordinators and district coordinators regarding its implementation. Overall, the teachers appeared positive about the Happiness Curriculum and found the curriculum very relevant in the present times.